Self-Efficacy Training to Reduce Work Stress in Member of The Police Ditsabhara Regional Police Special Region of Yogyakarta - Andy Arciana Dodik Setyawan Sukma; Kamsih Astuti; Siti Noor Fatmah (Jurnal Psikologi, 2020)
This study aims to determine the effect of self-efficacy training to reduce work stress on members of the Ditsabhra National Police DIY. The research subjects were 22 members of the National Police Ditsabhara who worked for a year. The research design used was the experimental design of pretest-posttest control group design. The number of experimental groups was 11 people and the control group was 11 people. Data collection tools used in the form of self-efficacy scale and work stress scale. Analysis of the data used is the Wilcoxon Rank Test to see the difference in the scores of the experimental group between before and after treatment and U-Mann Whitney to see the difference in scores between the experimental and control groups after self-efficacy training. Wilcoxon Rank Test results found that there were differences in job stress scores in the experimental group after being given a decrease in self-efficacy with a value of Z = -2.936 with a significance of 0.003 <0.05, which means that the experimental group's work stress level before getting higher self-efficacy training (X ̅ = 113.91 ) compared to the work stress level of the experimental group after being given self-efficacy training (X ̅ = 49.09). The results of U-Mann Whitney found that there were differences in work stress scores between the experimental group and the group with Z post test = -3.977 with p = 0.000 (p <0.001) which means that there was a significant difference in the work stress level between the experimental group and the control group , where the average work stress of the experimental group was lower (X ̅ = 49.09) than the average work stress of the control group (X ̅ = 112.55).